THE STRUCTURAL FEATURES OF THE HIGHER EDUCATION OF THE FRENCH REPUBLIC - Durdas, Alla (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the complex and multistage system of higher education in the French Republic. The main types of higher educational institutions in France and their peculiarities have been determined. A large variety of educational institutions, including specialized schools, have been emphasized in the article. The ability of French higher education establishments to be clearly oriented in the training of specialists for the requirements of the present has been specified in the article. The university education, consisting of several cycles, and the conditions for entering the institutions of higher education in France have been analyzed. The scale of grades has been outlined. A special system of French diplomas has been considered in the article. A role of grand schools in the French society has been stated. A national character of the French higher education has been specified in the article. The degrees of higher education in the French Republic and in Ukraine have been disclosed. The peculiarities and advantages of the French university education have been determined. Forms of organization of the educational process in the universities of France have been disclosed. A French analogue of the MBA has been described and the features of business education in the French Republic have been stated. The peculiarities of the specialized higher education in France have been outlined. The role and activities of the Agency for the Evaluation of Quality of Scientific Research and Higher Education in France have been determined. The regulatory bodies and the laws in the higher education systems in France and in Ukraine have been stated. A comparative analysis of the higher education systems of the French Republic and Ukraine has been carried out